Are the missing X-ray breaks in gamma-ray burst afterglow light curves merely hidden? - Curran, Peter; van der Horst, A.; Wijers, R. (Oxford University Press, 2008)
Gamma-ray burst (GRB) afterglow observations in the Swift era have a perceived lack ofachromatic jet breaks compared to the BeppoSAX or pre-Swift era. Specifically, relativelyfew breaks, consistent with jet breaks, are observed in the X-ray light curves of these bursts.If these breaks are truly missing, it has serious consequences on the interpretation of GRBjet collimation and energy requirements, and the use of GRBs as cosmological tools. Here,we address the issue of X-ray breaks that are possibly ‘hidden’ and hence the light curvesare misinterpreted as being single power laws. We do so by synthesizing X-ray telescope(XRT) light curves and fitting both single and broken power laws, and comparing the relativegoodness of each fit via Monte Carlo analysis. Even with the well-sampled light curves ofthe Swift era, these breaks may be left misidentified, hence caution is required when makingdefinite statements on the absence of achromatic breaks.